Robust heat-inducible gene expression by two endogenous hsp70-derived promoters in transgenic Aedes aegypti - Carpenetti, Tiffany L. G. (2011)
Aedes aegypti is an important vector of the viruses that cause dengue fever, dengue hemorrhagic fever, and yellow fever. Reverse genetic approaches to the study of gene function in this mosquito have been limited by the lack of a robust inducible promoter to allow precise temporal control over a protein-encoding or hairpin RNA transgene. Likewise, investigations into the molecular and biochemical basis of vector competence would benefit from the ability to activate an anti-pathogen molecule at specific times during infection. We have characterized the ability of genomic sequences derived from two Ae. aegypti hsp70 genes to drive heat-inducible expression of a reporter in both transient and germline transformation contexts. AaHsp70-luciferase transcripts accumulated specifically after heat shock, and displayed a pattern of rapid induction and decay similar to endogenous AaHsp70 genes. Luciferase expression in transgenic Ae. aegypti increased by ∼25-50 fold in whole adults by four hours after heat-shock, with significant activity (∼20 fold) remaining at 24 hr. Heat-induced expression was even more dramatic in midgut tissues, with one strain showing a ∼2500-fold increase in luciferase activity. The AaHsp70 promoters described could be valuable for gene function studies as well as for the precise timing of the expression of anti-pathogen molecules.